Associations of occupational standing with musculoskeletal symptoms: A systematic review with meta-analysis - Coenen, Pieter; Willenberg, L.; Parry, Sharon; Shi, J.; Romero, L.; Blackwood, Diana; Maher, C.; Healy, Genevieve; Dunstan, D.; Straker, Leon (BMJ Group, 2016)
Objective Given the high exposure to occupational standing in specific occupations, and recent initiatives to encourage intermittent standing among white-collar workers, a better understanding of the potential health consequences of occupational standing is required. We aimed to review and quantify the epidemiological evidence on associations of occupational standing with musculoskeletal symptoms. Design A systematic review was performed. Data from included articles were extracted and described, and meta-analyses conducted when data were sufficiently homogeneous. Data sources Electronic databases were systematically searched. Eligibility criteria Peer-reviewed articles on occupational standing and musculoskeletal symptoms from epidemiological studies were identified. Results Of the 11 750 articles screened, 50 articles reporting 49 studies were included (45 cross-sectional and 5 longitudinal; n=88 158 participants) describing the associations of occupational standing with musculoskeletal symptoms, including low-back (39 articles), lower extremity (14 articles) and upper extremity (18 articles) symptoms. In the meta-analysis, 'substantial' (>4 hours/workday) occupational standing was associated with the occurrence of low-back symptoms (pooled OR (95% CI) 1.31 (1.10 to 1.56)). Evidence on lower and upper extremity symptoms was too heterogeneous for meta-analyses. The majority of included studies reported statistically significant detrimental associations of occupational standing with lower extremity, but not with upper extremity symptoms. Conclusions The evidence suggests that substantial occupational standing is associated with the occurrence of low-back and (inconclusively) lower extremity symptoms, but there may not be such an association with upper extremity symptoms. However, these conclusions are tentative as only limited evidence was found from high-quality, longitudinal studies with fully adjusted models using objective measures of standing.